(untitled) (Research, Society and Development, 2019)
The school as a space for learning, social experiences and multiplicity plays a significant role in the formation of people, and also in social formation. The objective of this work is to reflect on the importance of the teaching role in the process of inclusion of students with visual impairment in the school context and in the teaching and learning process. For this, a bibliographic research was carried out. As a bibliographical research, we sought a critical analysis of the literature produced in the area, namely: De Masi (2000), Gil (2000) Masini (1993) and Ribeiro (2001). In the light of the authors, with regard to the education and inclusion of visually impaired students, it is concluded that the figure of the teacher is fundamental in the inclusive process of the visually impaired. For the educator, when sensitive to the inclusion process, knowing the need of his student, seeks adjustments to the curricular activities, as well as the adapted didactic materials necessary to provide equal learning, making the school an inclusive educational environment.